IBN MISKAWAIH'S THOUGHTS ON MORAL EDUCATION AND ITS RELEVANCE TO CONTEMPORARY ISLAMIC EDUCATION - ibadin, hasan; santosa, sedya (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
In this modern era, a lot of information has been spread in various media. The values contained in the information have two impacts, some are positive and some are negative according to the cultural traditions and values that exist in society. However, in reality now there are some Muslim communities in Islamic education itself that do not have the principles of appropriate values and morals. One of the Muslim philosophers who discussed moral philosophy named Abu Ali bin Muhammad bin Miskawaih or known as Ibn Miskawaih. He is famous as a philosopher and historian. The principle of the virtue of morality according to Ibn Miskawaih is based on the principle of al wasath or the middle. Al wasath is positioning oneself to be in the middle of neither the extreme right nor the extreme left, so that a person can be said to be just if he can place himself according to his needs. In addition, the thoughts initiated by Ibn Miskawaih about moral education are also still very relevant to contemporary Islamic education because there are many practices that have been applied in society, especially in boarding schools and educational institutions that practice the concept of moral education from Ibn Miskawaih, for example in schools every student is accustomed to applying the 5S habit, namely greetings, smiles, greetings, politeness and courtesy. Keywords: Thought, Ibn Miskawaih, Moral Education Translated with www.DeepL.com/Translator (free version)